Grammatical Errors on Descriptive Academic Writing - Sulaiman, Masagus; Syahri, Indawan (International Journal of Education Research and Development, 2022)
Generally, errors committed by EFL students in learning English at any level of study. This research focuses on university students who are taking Academic Writing course in the third semester. This research is aimed at identifying the types of errors and the dominant one committed by students in descriptive academic writing exercises. The method of the research was qualitative approach. The instrument that the researchers used in this research was through essay writing. There were 24 students were taken as subjects of the research. To analyse the data, the researchers used Error Analysis Method (EAM) based on Surface Structure Taxonomy and percentage error analysis. The findings showed that many students committed errors involving grammatical items in line with omission, addition, misinformation and misordering and the dominant was misordering error. The researchers assume that there were some factors that affects students’ errors such as lack of knowledge and competence in English grammar. In conclusion, error analysis method is such a suitable way to identify students’ errors using simple present tense in descriptive academic writing exercises.